Neurogenic Bowel Management in Traumatic Spinal Cord Injury – A Narrative Review - Sankha Subhra Roy; Margaret Chabungbam; Srikumar Venkataraman (Indian Journal of Physical Medicine & Rehabilitation, 2024)
Neurogenic bowel management in persons with spinal cord injury (SCI) is an important issue due to the associated morbidities causing a significant impact on the persons’ quality of life (QOL) and burden the caregiver and healthcare services. Complications such as constipation, diarrhoea, incontinence, social embarrassment and autonomic dysreflexia can be managed effectively and resourcefully to counter the ill effects. In India, the incidence of SCI is 15,000, with a prevalence of 0.15 million; most are educationally and economically underprivileged with substandard living conditions. Complications associated with neurogenic bowel tend to impede the implementation of vocational rehabilitation and community integration measures. The goals of management are to prevent complications and improve the QOL of persons with SCI. With the revolutionary progress in medical science, many pharmacological, non-pharmacological and surgical options have been formulated to satisfactorily and effectively manage the neurogenic bowel. In this narrative review, we have tried to compile some of the most popular and time-tested options for managing neurogenic bowel in persons with SCI.